Comparative evaluation of the lubricating properties of vegetable-oil-based nanofluids between frictional test and grinding experiment. (April 2017) - Wang, Yaogang; Li, Changhe; Zhang, Yanbin; Li, Benkai; Yang, Min; Zhang, Xianpeng; Guo, Shuming; Liu, Guotao; Zhai, Mingge
Highlights: Prejudge the lubricating properties of different nanoparticles by performing a frictional test. The grinding process was simulated by a ball-on-disc reciprocating tribotester. Test and verify the lubricating properties of the same nanofluids used in the grinding experiment. The frictional test can be used to prejudge the lubricating performance of the lubricants. Abstract: This paper presents the lubricating properties of different vegetable-oil-based nanofluids through a comparative evaluation between frictional test and grinding experiment. Two series of experiments were performed. The first experiment aimed to prejudge the lubricating properties of different nanofluids via a frictional test, which simulated the interface state of grinding between the abrasive grains and the workpiece. The second aimed to test and verify the lubricating properties of the same nanofluids through a grinding experiment. The mechanism of oil-film formation of nanofluids in the grinding zone was analyzed by morphology and element analysis of the worn surface. Overall, results indicate that all the nanoparticles can remarkably improve the lubricating properties of the base oil, and nanofluids effectively reduce sliding friction by forming a stable and low-friction film on the surface of friction pairs. In the frictional test, the average friction coefficient of Al2 O3 nanofluids decreased by 19.3%, and the mass wearing ratio increased by 65% compared with that of pure palm oil. The lubricating properties of different nanofluids in the frictional test were in good agreement with those in the grinding experiment. Thereby, the results can provide theoretical support and experimental guidance to explore the lubricating properties and film-formation mechanism of nanofluids in grinding zones. The results also prove that the Al2 O3 and MoS2 nanoparticles are suitable as anti-friction additives for machining lubricants.